EFEKTIVITAS PROGRAM KELUARGA HARAPAN DI KECAMATAN MUSTIKAJAYA KOTA BEKASI TAHUN 2025 - Sania Fitri Desinta; Rachmat Ramdani; Hanny Purnamasari (LPPM Universitas Abdurrab, 2025)
The Indonesia government is trying to protect the poor with various assistance one of which is the Family Hope Program, the purpose of which is to help the poor and vulnerable to social risks and its regulations are stated in the Minister of Social Affairs Regulation Number 1 of 2018. The purpose of this study is to determine the extent to which the target recipient are accurate and to know the systematic socialization and monitoring of the Family Hope Program in Mustikajaya District to measure the effectiveness of the Family Hope Program. This study uses a narrative method with a qualitative approach and collect data through interview. The results of this study indicate that the effectiveness of the Family Hope Program in Mustikajaya District is considered effective as seen from the benefits fel by beneficiary families, researches focus on indicators of target accuracy, program socialization, program objectives, and program monitoring